Development of Al-Qur'an Hadith Learning Media in the Form of a Board Book for Hijaiyah Letters Material at MIN Medan - Lubis, Indah Syafiq; Mardianto, Mardianto; Salminawati, Salminawati (UIN Sultan Aji Muhammad Idris Samarinda, 2024)
Teachers have steps to increase learning effectiveness, including designing open materials and learning media. The ability to develop learning tools needs to continue to be improved so that learning is more varied and prevents student boredom. This research proposes a solution by introducing hijaiyah letters to children through board books. With a research and development (R&D) approach, this research uses the ADDIE (Analysis-Design-Develop-Implement-Evaluate) model to create and test product effectiveness. Research Refers to the Reiser and Mollenda model for learning system design. By applying the ADDIE approach, this research includes a variety of data collection methods, including boardbook media trials, needs analysis, media development and media feasibility evaluation. Research instruments, such as validation sheets and student response questionnaires, were used to collect data in developing Al-Qur'an Hadith learning media in the form of boardbooks in class 1 at MIN 1 Medan City.